Green supply chain management: an advanced corporate environmental governance practice in an automotive case firm / Noor Sufiawati Khairani - Khairani, Noor Sufiawati (2015)
Green supply chain management [GSCM], recognised as an advanced corporate environmental governance [CEG] practice in this study, has gained widespread recognition as a corporate strategy to address firms’ environmental obligations. However, studies which examine this phenomenon in an accounting context are limited. The thesis addresses this gap in the literature by examining four fundamental GSCM issues: the procedure and practices involved in the GSCM deployment; the key CEG components for the deployment of GSCM; the development of environmental performance measurement system [e-PMS]; and, the role of accountants in the deployment of GSCM. The research issues are examined through a single case study, PROTON Tanjung Malim Sdn Bhd [PTMSB], a car manufacturing and assembly firm operating in Malaysia. . Drawing from the literature, a proposed interpretive GSCM framework is used to analyse and discuss the first research issue. As proposed in the Interpretive GSCM framework, the case findings affirm that the procedure-led Plan-Do-Check-Act [PDCA] ISO 14001 Environmental Management System [EMS] framework facilitates the deployment of GSCM at the case firm. The framework postulates ten GSCM practices associated with the procedure-led PDCA-ISO 14001 EMS framework. However, only six GSCM practices, viz green purchasing, green inbound logistics, green manufacturing, green building, green waste management, and inverse flow practice were found at PTMSB. The thesis next explores the fundamental CEG elements required for the deployment of GSCM. Towards this aim, a proposed interpretive e-5Ps CEG framework is used to analyse and discuss the findings.. The framework postulates five inter-linked CEG components namely environmental principle [e-Principle], environmental policy [e-Policy], environmental people/oversight [e-People], environmental process [e-Process], and environmental performance measurement system [e-PMS] for the deployment of GSCM. The results indicate that all five CEG elements are found in the case firm. However, the extent of application and commitment differs between these inter-linked elements. Furthermore, it is noted that several of the CEG elements are directly linked to the procedure-led PDCA -ISO 14001 EMS framework. Given that e-PMS is an element of the CEG framework, the thesis continues with the exploration of e-PMS at the case firm.. The findings indicate that procedure-based and measurement-based issues influence the development of the e-PMS. The procedure-based e-PMS is directly associated with the ISO 14001 EMS, suggesting a system-led development. A system-led e-PMS at PTMSB is supported by the needs-led, audit-led and model-led PMS procedures. Meanwhile, within the measurement-based perspective, several key environmental performance areas [KEPAs] identified within the case firm provide the direction for the development of key environmental performance indicators [KEPIs]. Finally, the thesis argues that the development of e-PMS fits closely with the role of management accountants. Despite these close parallels between the development of e- PMS and the management accountant’s role, the case findings found that management accountants have not responded appropriately to the potential opportunities for greater involvement in facilitating GSCM, particularly in the development of e-PMS.